Voices 2: Improving Prosodic Recognition in Schizophrenia With an Online Rehabilitation Program - Lado-Codesido, María; Rey Varela, Rosa María; Larios Quiñones, Marina; Martínez Agulleiro, Luis; Ossa Basanes, Julieta; Martínez Querol, María; Mateos, Raimundo; Spuch, Carlos; García-Caballero, Alejandro (Frontiers in Psychology, 2021)
Introduction: Emotion recognition of voices may play an important role in interpersonal communication and patients with schizophrenia present alterations in this regard. Several on-line rehabilitation tools have been developed for treatment in this area. Voices is an on-line prosodic recognition program consisting of identifying different emotional tones in neutral phrases, in different sessions of gradually increasing difficulty. This training tool has previously reported benefits, and a new version has been created called Voices 2. The main aim of this study is to test the capacity of the Voices 2 program to improve emotion recognition through prosody for adults with schizophrenia. Secondly, it seeks to observe durability effects 1 month after intervention. Method: A randomized, single-blind, multicenter clinical trial was conducted with 44 outpatients diagnosed with schizophrenia or schizoaffective disorder. The intervention group (also called Voices) was treated with Voices 2, whereas the control group was treated with auditory training that was not related to emotions. Sociodemographic and clinical data, clinical state (PANSS), Intelligence Quotient and prosodic recognition (RMV-SV) were measured at baseline. After intervention, RMV-SV and PANSS were assessed. One month later, the RMV-SV measure was repeated. Results: The control group (n = 19) and the Voices group (n = 22) did not differ on χ2, t or U tests in sociodemographic, clinical and psychometric variables at baseline or post-intervention (all p-values > 0.05). In the Voices group, statistically significant differences were observed in the RMV-SV scale applied post-intervention vs. that applied pre-intervention (Z = 2.47, p = 0.013). Similar results were observed in the 1-month follow-up RMV-SV vs. the pre-intervention RMV-SV (Z = 1.97, p = 0.049). PANSS scale was also assessed with no significant differences between pre vs. post measures in both groups. Lastly, Voices 2 was rated relatively higher, based on its ease of understanding, entertainment value, usefulness and the appropriateness of use of its emotional glossary. Discussion: Improvements were observed in prosodic recognition following intervention with Voices 2 in the Voices group. Although these results are similar to other clinical trial rehabilitation programs, specific research on the matter remains scarce. Certain aspects, such as the durability of effects or adherence should be thoroughly studied and clarified. Clinical Trial Registration: [https://doi.org/10.17605/OSF.IO/G95C4].